Intercontinental trans-boundary contributions to ozone-induced crop yield losses in the Northern Hemisphere - M. J. Hollaway; S. R. Arnold; A. J. Challinor; L. D. Emberson (Biogeosciences, 2012)
Using a global atmospheric chemistry model, we have quantified for the first time, intercontinental transboundary contributions to crop ozone exposure and subsequent yield reductions in the Northern Hemisphere. We apply four metrics (AOT40, M7, M12, W126) to assess the impacts of 100% reductions in anthropogenic NOx emissions from North (N) America, South East (SE) Asia and Europe on global and regional exposure of 6 major agricultural crop types to surface ozone, and resultant crop production losses during the year 2000 growing season. Using these metrics, model calculations show that for wheat, rice, cotton and potato, 100 % reductions in SE Asian anthropogenic NOx emissions tend to produce the greatest global reduction in crop production losses (42.3–95.2%), and a 100 % reduction to N~American anthropogenic NOx emissions results in the greatest global impact on crop production losses for maize and soybean (59.2–85.9%). A 100% reduction in N~American anthropogenic NOx emissions produces the largest transboundary impact, resulting in European production loss reductions of between 14.2% and 63.2%. European NOx emissions tend to produce a smaller transboundary impact, due to inefficiency of transport from the European domain. The threshold nature of the AOT40 ozone-exposure metric results in strong dependence of non-local emissions impacts on the local ozone concentration distribution. Our calculations of absolute crop production change under emission reduction scenarios differ between the metrics used, however we find the relative importance of each region's transboundary impact remains robust between metrics. Our results demonstrate that local air quality and emission control strategies have the potential to partly alleviate ozone-induced crop yield loss in continents downstream, in addition to effectively mitigating local ozone-induced production losses.